2008
DOI: 10.1002/cncr.23629
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatments do not alter the quality of life in elderly patients with colorectal cancer

Abstract: BACKGROUND. The current study was performed to longitudinally assess the impact of adjuvant treatments on the quality of life (QoL) of elderly colorectal cancer survivors. METHODS. The Burgundy Digestive Cancer Registry was used to select all patients aged ≥75 years who were diagnosed with colorectal cancer between 2003 and 2005. A total of 209 patients were asked to complete questionnaires during the first year after diagnosis: at the time of inclusion in the study (Q0), at 3 months after the initial diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 30 publications
5
37
0
Order By: Relevance
“…Also, patients might accept a certain amount of adverse events that may negatively impact their HRQoL, because of the expected health and treatment outcomes related to this therapy. This assumption is in line with previous findings from other studies [9,23,29]. Third, our results could be influenced by a survivorship bias.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, patients might accept a certain amount of adverse events that may negatively impact their HRQoL, because of the expected health and treatment outcomes related to this therapy. This assumption is in line with previous findings from other studies [9,23,29]. Third, our results could be influenced by a survivorship bias.…”
Section: Discussionsupporting
confidence: 93%
“…Maybe fear of recurrence of cancer is a more distinct feature in younger cancer patients while elderly patients may be aware that with ageing, one or more diseases will evolve [22]. Most studies on HRQoL among elderly colorectal cancer patients report a decline of HRQoL as age increases [10,[23][24][25][26][27]. Data of a French study suggest a parallel decline of HRQoL in the general healthy population but the authors did not analyse this age-related relationship [28].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of HRQoL over time in patients with colorectal cancer was also shown in a previous study (Bouvier et al, 2008;Hulbert-Williams et al, 2012;Sun et al, 2012). Our results also demonstrated that colorectal cancer patients show deterioration in HRQoL during the treatment period.…”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation for this is the more severe side effects experienced during treatment. However, Bouvier (2008) documented that adjuvant chemotherapy for colon cancer has no longterm negative impact on the QoL of elderly patients. The increased deterioration in HRQoL during treatment and improvement in the longer-term need to be documented in future population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the wide consensus on its effectiveness since 1990, we did not expect to find that such a strong recommendation would be so poorly followed. Comorbidity and greater toxicity are not valid reasons for the underuse of adjuvant chemotherapy in the elderly: toxicity is not greater24 25 and quality of life is not worse 26…”
Section: Discussionmentioning
confidence: 99%